2015
DOI: 10.1007/s11665-015-1565-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Gas Sensing Applications of WO3 Nanobricks

Abstract: WO 3 nanobricks are fabricated by a simple hydrothermal method. Morphology and structure of the WO 3 nanobricks are characterized by scanning electron microscopy and x-ray diffraction. Gas sensing properties of the as-prepared WO 3 sensor are systematically investigated by a static gas sensing system. The results show that the WO 3 nanobricks with defect corners demonstrate good crystallinity, and the mean edge length and wall thickness are 1-1.5 and 400 nm, respectively. The WO 3 sensor achieves its maximum s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Xiao and Song proposed a DFL method using outlier link rejection. (3) Owing to the uncertainty of a wireless channel, certain links may be seriously polluted, resulting in error detection. The authors first identified the outlier link and then rejected this link to reduce the error induced by it.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Xiao and Song proposed a DFL method using outlier link rejection. (3) Owing to the uncertainty of a wireless channel, certain links may be seriously polluted, resulting in error detection. The authors first identified the outlier link and then rejected this link to reduce the error induced by it.…”
Section: Related Workmentioning
confidence: 99%
“…Researchers have proposed DFL systems using different technologies such as RF, (1)(2)(3) camera, (4) infrared, (5) and ultrasonic. (6) Radio frequency (RF)-based schemes have advantages of long range, low cost, and the ability to work through nonconducting walls and obstacles.…”
Section: Introductionmentioning
confidence: 99%